The construction of a new oncolytic herpes simplex virus expressing murine interleukin‐15 with gene‐editing technology. Issue 12 (14th February 2020) - Cai, Linkang; Hu, Han; Duan, Haixiao; Li, Yuying; Zou, Zongxing; Luo, Kailun; Zhang, Ziyi; Yang, Junhan; Jin, Jing; Chen, Ying; Ke, Zonghuang; Fang, Zongyao; et al.
Abstract: The treatment of tumors with oncolytic viruses is an important cancer immunotherapy strategy. Interleukin‐15 (IL‐15) can enhance the antitumor effect of natural killer cells and T cells. An oncolytic herpes simplex type II virus (oHSV2‐mIL‐15CherryFP) expressing mouse IL‐15 was constructed using the CRISPR/Cas9 system, and its antitumor activity in vitro and in vivo was evaluated. In vitro, the mouse interleukin‐15 (mIL‐15) present in the culture supernatant expressed by oHSV2‐mIL‐15CherryFP was able to enhance the killing of CT26‐GFP tumor cells by T cells. In addition, the intratumoral injection of oHSV2‐mIL‐15CherryFP inhibited tumor growth in the CT26‐iRFP and BGC823‐iRFP model. These results indicate that the use of oncolytic herpes simplex virus expressing IL‐15 may be a potential therapeutic strategy in tumor immunotherapy. Highlights: CRISPR/Cas9 system can be used and induce NHEJ in oHSV2 gene editing. Expression of natural mouse IL‐15 can enhance oHSV2 antitumor immunotherapy in vivo.